All's well that ends well: the timing of floral meristem termination. Issue 2 (18th January 2023) - Min, Ya; Kramer, Elena M.
Summary: Floral meristem termination (FMT) represents one of the defining features of a floral meristem relative to a vegetative meristem. Timing of FMT is a major determinant of the total number of organs in a flower, and canalization toward relatively rapid FMT is considered to have been a major force in shaping angiosperm evolution. For decades, investigation of FMT has been focused on model systems that only produce four whorls of organs in a flower, while little is known about the molecular basis that underlies nature variation in the timing of FMT. Here, we hypothesize on how known pathways could have been modified to generate variation in FMT and explain how developing new model systems will help to deepen our understanding of the genetic control and evolution of FMT.